2019
DOI: 10.3390/ani9110998
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cadmium Chloride Supplementation Impairs Renal Function and Bone Metabolism of Laying Hens

Abstract: Simple SummaryIn this study, the effects of cadmium (Cd) on renal function and bone metabolism of laying hens were investigated. Results indicated that supplementation with Cd can damage renal function, induce oxidative stress in the kidney, disrupt the body’s calcium balance and hormone secretion, and negatively affect bone metabolism of laying hens. The results demonstrated that chronic exposure to Cd could induce renal dysfunction and bone damage in laying hens.AbstractThis study was conducted to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Our results assure the prophylactic potential of ascorbic acid or clay to prevent or decrease cadmium-induced toxic manifestations. ALP in blood is considered as an indicator of mineral status and bone mineralization especially Ca and P which plays an important role in the homeostasis of the body and ensures appropriate conditions for biological activities such as energy utilization, nucleic acid synthesis and bone mineralization [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our results assure the prophylactic potential of ascorbic acid or clay to prevent or decrease cadmium-induced toxic manifestations. ALP in blood is considered as an indicator of mineral status and bone mineralization especially Ca and P which plays an important role in the homeostasis of the body and ensures appropriate conditions for biological activities such as energy utilization, nucleic acid synthesis and bone mineralization [52].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that dietary Mn deficiency reduces tibia bone quality by decreasing Tb.N, Tb.Th, and increasing Tb.Sp in broilers ( 24 ). Dietary cadmium chloride supplementation impairs bone metabolism by increasing Tb.Sp and decreasing Tb.N in laying hens ( 25 ). Probiotic addition into the diet of laying hens improved tibia and femur quality by increasing BMD and bone mineral content ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in rats showed that exposure to cadmium and lead decreased calcitonin levels [ 243 , 247 ]. Exposure of laying hens to cadmium led to a decrease in calcitonin levels [ 248 ], while a study in goldfish found no changes in calcitonin levels after cadmium exposure (although exposure to methylmercury increased calcitonin levels) [ 249 ].…”
Section: Environmental Factors That Affect Pth and Calcitonin Levelsmentioning
confidence: 99%